A multi-channel MAC for multi-hop wireless sensor networks minimizing hidden node collision - Murdiyat, P.; Chung, K.; Chan, King-Sun (2016)
Employing multiple channels to improve the multi-hop wireless network performance has recently attracted a lot of attention. Given that hidden node collision is a key cause of the performance degradation in multi-hop wireless networks, we propose a solution to minimize the hidden node collision probability. It involves the use of a coordination mechanism, which tries to assign different frequency channels to two nodes that may be involved in hidden node collision. Also, a reserved bit in 802.11 MAC frame format is used to coordinate the channel assignments thereby minimizing the scheme's overhead. Simulation results show that an improved throughput can be achieved with our proposed scheme.